Saving lives during the COVID-19 pandemic: The benefits of the first Swiss lockdown - Nicolò Gatti; Beatrice Retali (Swiss Journal of Economics and Statistics, 2021)
The implementation of a lockdown to control the spread of the COVID-19 pandemic has led to a strong economic and political debate in several countries. This makes it crucial to shed light on the actual benefits of such kind of policy. To this purpose, we focus on the Swiss lockdown during the first wave of COVID-19 infections and estimate the number of potentially saved lives. To predict the number of deaths in the absence of any restrictive measure, we develop a novel age-structured SIRDC model which accounts for age-specific endogenous behavioral responses and for seasonal patterns in the spread of the virus. Including the additional fatalities which would have materialized because of the shortage of healthcare resources, our estimates suggest that the lockdown prevented more than 11,200 deaths between March and the beginning of September 2020.
Keywords: I18; D91; H12; 330; COVID-19; Lockdown; Saved lives; SIRDC model; SIR model; Behavioral responses